From tokenism to meaningful engagement: best practices in patient involvement in an EU project. Issue 1 (December 2015) - Supple, David; Roberts, Amanda; Hudson, Val; Masefield, Sarah; Fitch, Neil; Rahmen, Malayka; Flood, Breda; de Boer, Willem; Powell, Pippa; Wagers, Scott
Plain English summary This commentary talks about patient involvement in one of the biggest EU projects to date—U-BIOPRED. It describes how people and carers of people with asthma have been able to develop and drive their input and have their voice heard among the >200 healthcare professional project members. Five key principles for the success of the patient involvement group are presented: involve early, involve deeply, have patients feedback on project progress, include patients in dissemination and help patients convey their own story. This group has been used as an example for other EU-funded projects, and the patient involvement group will be maintained after the end of the project to ensure that their experience and knowledge can help develop best practice in the future.